Effort to Increase Performance of Sub Directorate of State Revenue of Mineral and Coal in Optimizing Non Tax State Revenue General Mining - Hasibuan, Mikko Rawindra; Djajadiningrat, Surna Tjahja (The Indonesian Journal of Business Administration, 2012)
Non Tax State Revenue of Natural Resources of General Mining which managed by Sub Directorate of State Revenues of Mineral and Coal consist of Dues Remain and Royalty paid by Mining License Holder, consist of Contract of Work, Coal Mining Agreement and Mining Authority or Mining License. In managing Non Tax State Revenues divided two section with planning task, evaluation, verification and stipulation of result of Non Tax State Revenues task, with administration task as supporting. The bigger workload are evaluate and verify the Dues Remain and Royalty document.Â In line with demand increase of mining commodities the number of Business Permit of Mining especially Mining Authority (KP) and Mining License (IUP) had increased significantly, so workload of evaluating and verifying Dues Remain and Royalty also had increased.Â To know the needs of the number of employees first calculate the number of workload, or the number of Dues Remain and Royalty documents that will be sent by all Mining Authorities with quantitative method of regression analysis is supported by a survey to know employee productivity. Regression analysis showed that if the number of KP / IUP reaches 6951, the number of Dues Remain documents will reach 10535 and the sales transaction document (Royalties) 19539 units. Based on employee productivity in order to that the large number of documents of Dues Remain and Royalty of the Mining Authority or Mining License can be handled properly it is necessary addition 7 employees, for verification to the field required 14 employees and for the reconciliation in the framework production planning and the stipulation of Non Tax State Revenues required seven employees.Â Effectiveness of organization of Sub Directorate of State Revenues of Mineral and Coal, learned of whether the appear workload could be handled as well as whether every structure have done tasks in a focused and not mixed with other tasks. Based on that thing, in order to there is a separation of task well it is necessary addition become 4 organizational structure as level as section, that are the structure determination of the planning and realization of Non Tax State Revenues, the two structures recording, evaluation and verification of Non Tax State Revenues, as well as a structure administration. Keywords: job analysis, workload analysis, organizational structure, human resource planning, recruitment